White-Light Emission and Tunable Luminescence Colors of Polyimide Copolymers Based on FRET and Room-Temperature Phosphorescence - Nara, Mayuko (ACS Omega, 2020)
[Image: see text] Thermally stable copolyimide (CoPI) films exhibiting high optical transparency and room-temperature phosphorescence (RTP) were prepared by copolymerizing fluorescent dianhydride and brominated phosphorescent dianhydride with an alicyclic diamine. The CoPI films underwent a 5 wt % degradation at a temperature higher than 349 °C and exhibited dual fluorescent and phosphorescent emissions owing to their efficient Förster resonance energy transfer from the fluorescent to phosphorescent dianhydride moieties in the main chains, followed by an intersystem crossing from the singlet to triplet state of the latter moiety atoms. The CoPIs displayed bright RTP under a vacuum with various colors produced when adjusting the copolymerization ratio. CoPI with 5 mol % phosphorescent moiety (CoPI-05) emitted white light with high optical transparency owing to the suppression of the PI chain aggregation that causes a yellowish coloration. The copolymerization of fluorescent and phosphorescent PI moieties can control the photoluminescent properties of PI films and is applicable to color-tunable solid-state emitters, ratiometric oxygen sensors, and solar-spectrum converters.